Copper(II) complexes inducing apoptosis in cancer cells, and demonstrating DNA and HSA interactions. (16th August 2017) - Hu, Jiyong; Liao, Chunli; Guo, Yan; Yang, Fan; Sang, Wei; Zhao, Jin'an
Graphical abstract: Copper complexes1 and2 possess anticancer activity toward several human tumor cell lines, and the activity of complex1 was investigated in-depth. Absorption spectral titration and ethidium bromide displacement assays showed that1 has strongly affinity towards DNA. Complex1 can pass through cell membrane and accumulate in nuclei and mitochondria, which activates the intracellular ROS generation and leads to DNA fragmentation. Moreover, complex1 blocks cell cycle in G0/G1 phase and induces mitochondrial transmembrane potential dissipation, leading to HCT116 cells apoptosis. Additionally, protein binding ability of this complex was analyzed by the static quenching of HSA emission. Abstract: To study the mechanisms underlying the toxicity of benzimidazole-based copper (Cu) complexes based on their molecular structure, [Cu2 (bpbmb)Br4 (CH3 OH)4/3 ]2 ·(CH3 OH)4 (1 ) and Cu2 (bpbmb)Cl3 ·(CH3 O) (2 ) were synthesized through the reaction between 4, 4′-bis ((2-(pyrazin-2-yl)-1H-benzoimidazol-1-yl)methyl)-1, 1′-biphenyl (bpbmb) and Cu salts. Complexes1 and2 showed potent in vitro cytotoxicity against four human tumor cell lines (BGC823, HT29, HCT116, and SMMC7721), especially against HCT116 cells. Furthermore, the activity of complex1 was investigated in-depth. Absorption spectral titration and ethidium bromide displacement assays revealed that complex1 shows affinity towards DNA. Complex1 was found to cleave pBR322 DNA in the presence of ascorbic acid, and to pass through the cell membrane and accumulate in cell nuclei and mitochondria, damaging DNA, which was confirmed by inductively coupled plasma mass spectrometry (ICP-MS) and comet assay. The generation of increased intracellular reactive oxygen species (ROS) levels was observed in complex1 treated cells, compared with those determined in the untreated control. Flow cytometric analyses indicated that complex1 can inhibit the growth of tumor cells through G0/G1 cell cycle arrest, mitochondrial transmembrane potential dissipation, and the induction of apoptosis. Moreover, protein binding ability of this complex was analyzed by the static quenching of human serum albumin (HSA) emission. These results indicated that complex1 acts as a potent anticancer agent, inducing the apoptosis of HCT116 cells by promoting DNA damage, mitochondrial dysfunction, and ROS production.